3 UMPSA Cadet Officers crowned Best PALAPES Cadets - Naqiah, Puaad (UMPSA, 2024)
PEKAN, 24 September 2024 – Three cadet officers from the PALAPES unit at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) were recently awarded the highest honours as Best Cadet Officers in the categories of Army, Navy, and Air Force at the 42nd Royal Commissioning Ceremony of Cadet Officers from Public Universities (UA), held at Universiti Pendidikan Sultan Idris (UPSI).